Resíduo de madeira: um estudo exploratório do potencial industrial para o desenvolvimento de novos revestimentos - PETRUS, Andréa Souza Saad (2022)
By using wood waste species, the consumer may encounter the use of a noble raw material that reduces the exploitation of certain species. In this context, what are the characteristics of wood residues that help in the development of new coatings? Therefore, it is proposed as an analyze the characteristics of these residues in São Luís – MA and Vocational Unit – Shipyard School, for manufacture of new coatings, identifying the theoretical contribution for the sustainable use of this material, analyzing and mapping the wood residues, identifying through its database its physical, mechanical and organoleptic characteristics, as well as prototyping a new coating with the use of compatible woods studied for this purpose. The approach is qualitative, and the objectives are descriptive-exploratory. The result is the composition of a theoretical substrate on the sustainable potential of the wood residue.